Spinale Mammakarzinommetastasen aus Sicht der Wirbelsäulenchirurgie: Prädiktoren auf Molekularebene zur Wahl der adäquaten Therapiestrategie - Adler, Daniel; Sinn, Peter; Schneeweiss, Andreas; Al Mansour, Haidara; Lehner, Burkhard; Akbar, Michael; Kriegsmann, Mark (Der Orthopäde, 2018)
Breast cancer is the most common malignancy affecting women and the spinal column is most likely affected by metastases. Modern oncologic treatment options have significantly prolonged survival times in the last decade. Therefore, treatment of vertebral metastases has been of special interest in spine surgery. Different scores are described to evaluate prognosis and to choose correct treatment strategies, which however only differentiate tumor entities and not specific tumor phenotypes. Breast cancer has been classified into five intrinsic subtypes with different survival rates since the turn of the millennium. The aim of this review was to describe molecular predictors of breast cancer malignancy and to better estimate expected survival times and invasiveness of therapies with regard to spinal metastases.
Gesehen am 02.05.2019